Evaluating the Quality and Reliability of Gender-affirming Surgery Videos on YouTube and TikTok. Issue 7 (28th July 2022) - Song, Siyou; Park, Keon Min; Phong, Kiet; Kim, Esther A.
Abstract : Background: Social media platforms have changed the way medical information is disseminated. Transgender patients may utilize social media to learn about gender-affirming surgery (GAS). Although videos on social media are readily accessible, their content is not verified or peer-reviewed. Therefore, this study aimed to evaluate the quality and reliability of YouTube and TikTok videos related to GAS. Methods: YouTube and TikTok were queried for gender-affirming top surgery, metoidioplasty, phalloplasty, breast augmentation, and vaginoplasty. Quality of video content was analyzed by the DISCERN scale. Quality scores were compared among the type of GAS, account user, and content category. Results: There were 275 YouTube videos and 55 TikTok videos. Most videos focused on masculinizing top surgery ( P < 0.001). Overall, videos on masculinizing GAS had higher quality and reliability than videos on feminizing GAS ( P < 0.001). Chest surgery videos were of higher quality than those on genital surgery ( P ≤ 0.001). Videos on masculinizing top surgery had the highest quality, whereas vaginoplasty had the lowest quality and reliability ( P < 0.001). Videos produced by health care professionals and academic institutions had the greatest quality and reliability, respectively ( P < 0.0001), whereas videos produced by patients were the least reliable ( P < 0.0001). Conclusions: Videos on GAS ranged from poor to good quality and reliability. Health care professionals, especially plastic surgeons, should create high-quality videos on social media to educate transgender patients. There should also be greater efforts in disseminating existing high-quality videos on social media. Resources posted on social media platforms can reach a wide audience through accessible means.